The Relationship Between Learner Characteristics and Student Outcomes in a Middle School Computing Course: An Exploratory Analysis Using Structural Equation Modeling. Issue 1 (2nd January 2019) - Ketenci, Tuba; Calandra, Brendan; Margulieux, Lauren; Cohen, Jonathan
Abstract: This study, which took place during a 7-week middle school computing course, used structural equation modeling to examine the overall cumulative relationship between self-efficacy, interest, and prior computing experience and students' computer science learning outcomes. The findings indicated that 52% of the variance of student success, measured by a computational thinking quiz and rubric-based evaluations of participants' computing artifacts, was related to the aforementioned learner characteristics. These findings have implications for theory and practice and suggest that future research and instructional design practice in K–12 computing education should take these learner characteristics into account.